1992
DOI: 10.1093/nar/20.11.2647
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for binding of a 40 kDa protein to the leaders of yeast mitochondrial mRNAs

Abstract: An abundant yeast mitochondrial 40 kDa protein (p40) binds with high specificity to the 5'-untranslated region of cytochrome c oxidase subunit II (COX2) mRNA. Using mobility shift and competition assays, we show here that purified p40 complexes with the leaders of all eight mitochondrial mRNAs of Saccharomyces cerevisiae. The location of the protein binding site on the different leaders is not conserved with respect to the AUG start codon. In vitro RNA footprint and deletion experiments have been used to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…The eighth mRNA encodes VAR1, a hydrophilic component of mitochondrial ribosomes. In the compact 5′-untranslated region of the COX2 transcript (Figure 1) (13) have suggested that binding of this soluble matrix enzyme might repress translation until an appropriate association between the mRNA and hydrophobic elements in mitochondrial membranes is attained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eighth mRNA encodes VAR1, a hydrophilic component of mitochondrial ribosomes. In the compact 5′-untranslated region of the COX2 transcript (Figure 1) (13) have suggested that binding of this soluble matrix enzyme might repress translation until an appropriate association between the mRNA and hydrophobic elements in mitochondrial membranes is attained.…”
Section: Discussionmentioning
confidence: 99%
“…The holoenzyme binds sequences near potentially conserved secondary structures within the 5′ untranslated regions of all eight major yeast mitochondrial mRNA transcripts (13). Both IDH subunits are necessary for this RNA binding (12).…”
mentioning
confidence: 99%
“…Suv3 is part of the mitochondrial RNA degradosome and is also involved in mitochondrial DNA maintenance and COX1 aI5␤ intron splicing (52)(53)(54). (NAD ϩ )-dependent isocitrate dehydrogenase is known to bind in vitro to mitochondrial mRNAs and probably can modulate translation (55)(56)(57)(58). In addition to the three described roles for Pet54, it could be possible that this protein has some function in the assembly of the CcO because it has been detected in supercomplexes (59).…”
Section: Discussionmentioning
confidence: 99%
“…For isocitrate dehydrogenase, however, it is as yet unclear why two so disparate activities are combined in a single protein. It has previously been speculated that p40 may act as a translational repressor [92]. Such a role would account for the finding that chimeric mRNAs apparently lacking p40 binding sites are still translatable and goes some way towards explaining why p40 disrupted strains maintain the ability to grow (albeit slowly) on certain non-fermentable substrates [94].…”
Section: Yeast Mitochondrial Nad+-dependent Isocitrate Dehydrogenase mentioning
confidence: 99%
“…An additional protein that specifically interacts with leader sequences of all major mRNAs has been identified by a biochemical approach [91,92]. This 40 kDa protein (p40) is nuclear encoded, exclusively present in mitochondria and highly abundant [93].…”
Section: Yeast Mitochondrial Nad+-dependent Isocitrate Dehydrogenase mentioning
confidence: 99%